2021
DOI: 10.3390/jcm10215090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neuromuscular Blockade on Intraoperative Respiratory Mechanics and Surgical Space Conditions during Robot-Assisted Radical Prostatectomy: A Prospective Randomized Controlled Trial

Abstract: The aim of this study was to investigate whether deep neuromuscular blockade (NMB) may affect intraoperative respiratory mechanics, surgical condition, and recovery profiles in patients undergoing robot-assisted radical prostatectomy (RARP). Patients were randomly assigned to the moderate or deep NMB groups. Pneumoperitoneum was maintained with carbon dioxide (CO2) insufflation at 15 mmHg during surgery. The primary outcome was peak inspiratory pressure (PIP) after CO2 insufflation. Mean airway pressure (Pmean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to a meta-analysis [11] on the effects of deep NMB in laparoscopic abdominal surgery, it was proven that deep NMB reduces early postoperative pain and improves the surgical condition during laparoscopic abdominal surgery. Additionally, two randomized, controlled trials [25,26] reported that deep NMB improves surgical condition during robot-assisted radical prostatectomy. However, to our knowledge, there has been no study that investigated the effect of deep NMB in RATT.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis [11] on the effects of deep NMB in laparoscopic abdominal surgery, it was proven that deep NMB reduces early postoperative pain and improves the surgical condition during laparoscopic abdominal surgery. Additionally, two randomized, controlled trials [25,26] reported that deep NMB improves surgical condition during robot-assisted radical prostatectomy. However, to our knowledge, there has been no study that investigated the effect of deep NMB in RATT.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies were judged to be at low risk of bias [17,23,26,28,31,40,53], 23 studies were judged to raise some concerns [12, 15, 16, 19, 24, 29, 32, 34, 36, 38, 41-47, 49-52, 54, 55], and 10 studies were judged to be at high risk of bias [13,14,25,27,30,33,35,37,39,48]. The details of judgments for each risk-of-bias domain are demonstrated in Fig 2.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…Adverse events. Twenty-one studies reported specific perioperative adverse events, which included but were not limited to vascular and organ injury [39,44,49], respiratory complications [14,23,34,35,39,40], cardiovascular complications, digestive complications [34], postoperative nausea and vomiting [17,30,31,33,38,40,41,44,48,50,52,53], incision complications [46], postoperative delirium [17], and shoulder pain [27,38,47]. The sample size was small, and the adverse events varied.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations